2013
DOI: 10.15560/9.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Insular Anurans (Amphibia: Anura) of the coast of Rio de Janeiro, Southeast, Brazil

Abstract: Herein we present the first lists of anuran species of five islands off the coast of Rio de Janeiro State, Brazil, and updated lists for two other islands (Ilha Grande and Ilha da Marambaia). These lists resulted from thorough searches of the literature and of herpetological collections databases, and from surveys on the islands conducted between March 2009 and January 2011. Currently there are 49 species of anurans distributed in 10 families recorded for these islands and this number accounts for c. 90% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…Finally, the record of Ololygon perpusilla is probably referable to an apparently undescribed species of the O. perpusilla group (referred to as Scinax gr. perpusillus by Bittencourt-Silva & Silva, 2013).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Finally, the record of Ololygon perpusilla is probably referable to an apparently undescribed species of the O. perpusilla group (referred to as Scinax gr. perpusillus by Bittencourt-Silva & Silva, 2013).…”
Section: Resultsmentioning
confidence: 98%
“…Ischnocnema -Ischnocnema octavioi was first reported for Ilha Grande by Rocha et al (2000Rocha et al ( , 2001, but that record was later found to be based on two misidentified specimens of I guentheri (Vrcibradic et al, 2008). Bittencourt-Silva & Silva (2013) reported the occurrence of I octavioi in Ilha Grande based on a third specimen, MNRJ 60158 (the two previously mentioned specimens, MNRJ 47972-73, were correctly listed by them under I guentheri). The specimen MNRJ 60158 was collected by a colleague and is, in fact, I octavioi, which confirms the occurrence of this species in the island.…”
Section: Cycloramphus -Bothmentioning
confidence: 99%
See 2 more Smart Citations
“…2004). According to available literature, almost all previous records of I. octavioi are from the state of Rio de Janeiro, including the type locality, Estrada da Cascatinha, Tijuca Mountains (Bokermann 1965, Costa et al 2008, Vrcibradic et al 2008, Siqueira et al 2009, Ouvernay et al 2012Bittencourt-Silva & Siva 2013, Almeida-Gomes et al 2014a, Martins et al 2014. One exception is the record from Espírito Santo state, but this record probably based on I. verrucosa (Reinhardt & Lütken, 1862), a species with very similar characteristics to I. octavioi but having a different distribution (Dantas & Ferreira 2010).…”
mentioning
confidence: 99%